Gastrointestinal safety of novel nonsteroidal antiinflammatory drugs: selective COX-2 inhibitors and beyond - Coruzzi, G.; Venturi, N.; Spaggiari, S. (Acta Biomedica Atenei Parmensis, 2007)
Nonsteroidal antiinflammatory drugs (NSAIDs) are frequently associated with adverse reactions, related to inhibition of cyclooxygenase (COX) in tissues where prostaglandins exert physiological effects, such as gastric mucosal defense and renal homeostasis. The discovery of two COX isoforms, namely COX-1 constitutively expressed in most tissues and COX-2 induced at sites of inflammation, led to the development of selective COX-2 inhibitors (“coxibs”), with the hope of significantly reducing the gastrointestinal toxicity associated with acute and chronic NSAID use. However, the increased knowledge of physiological roles of COX-2 enzyme in a variety of tissues, including stomach and kidney, together with the withdrawal from the market of rofecoxib and valdecoxib because of cardiovascular toxicity, have challenged the benefits of selective COX-2 inhibition. As a consequence, the interest for novel approaches has re-emerged; new therapeutic options, still under clinical evaluation, are represented by dual COX and 5-lipooxygenase (5-LOX) inhibitors, synthetic lipoxins, nitric oxide (NO)-releasing NSAIDs and, more recently, by NSAIDs releasing hydrogen sulphide (H2S). This review focuses upon the gastrointestinal (GI) safety of selective COX-2 inhibitors and of novel therapeutic strategies, in comparison with traditional NSAIDs.